The directorate and its contribution to teaching performance in pre-university preparation institutions - Canales Torres, Fátima Elizabeth (2020)
The aim of this research is to determine the correlation between management and teaching performance in pre-university academies. A sample of 55 teachers was selected. It was developed a non-experimental field work in a descriptive-correlational cross-sectional or transectional method. The results were analyzed by using the IBM SPSS statistical program. To collect the information, the survey technique used a Likert-type scale. A result of, 624 was obtained; concluding that there is a significant positive relationship between leadership and teacher performance and good communication. That is the reason why a good management process is important to obtain a positive response from teachers.